Modelling of Saltwater Intrusion into a Discharging Well in a Non-Homogeneous Unconfined Aquifer - Ghazali, Abdul Halim; Jong, Tze Yong; Muyibi, Suleyman Aremu; Said, Salim; Eloubaidy, Aziz F. (Universiti Putra Malaysia Press, 2003)
Finite element method based on the Galerkin technique was used to formulate the solution for simulating a two-dimensional transient movement of saltwater in a stratified aquifer under pumping conditions. The aquifer system was unconfined, non-homogeneous and isotropic. The groundwater flow and convection-dispersion equations were transformed into two non-linear coupled partial differential equations to yield the values of the corresponding piezometric head and saltwater concentration at various points and times. These two equations were solved by Argus- ONE™ SUTRA model that employs the finite element method. The performance of the numerical model is compared with the data observed from a laboratory experimental model. Good agreement has been achieved between the numerical and experimental models for the concentration and hydraulic head as comparison showed the maximum differences of only 10% and 11% respectively.